The Influence of information transparency and disclosure on the value of listed companies: Evidence from Vietnam - Loc Dong Truong; Thai Xuan Le; H. Swint Friday (Journal of Risk and Financial Management, 2022)
This analysis examines the influence of information transparency and disclosure on the value of companies listed on the Vietnamese stock market. Data employed in this study were primarily gathered from the audited financial statements, management reports and other related documents of 430 publicly traded firms listed on the Ho Chi Minh Stock Exchange (HOSE) and Ha Noi Stock Exchange (HNX) for the time period from 2014 through 2016. Using the GMM (Generalized Method of Moments) approach, the empirical findings indicate that the level of transparency and disclosure of the companies has a significant positive effect on firm value as measured by Tobin's Q.
Keywords: G11; G32; G34; 650; transparency and disclosure; value of listed companies; Vietnam